PENGARUH KERJASAMA GURU DENGAN ORANGTUA MURID TERHADAP PENINGKATAN AKTIVITAS BELAJAR SISWA - Munte, Bangun (Jurnal Dinamika Pendidikan, 2015)
The role of parents in the family is crucial in shaping the future of their children as well as education which in essence is a human effort to humanize the man himself. The position of teachers as educators and counselors are not only with teaching materials that are used but with his whole personality. In addition, the private teacher is a unity between personal traits as educators, teachers and counselors, and can be interpreted as an example or role model. The method used is descriptive research that is deliberately designed to analyze and interpret data and determine the relationship or influence of independent variables on the dependent variable, and then draw conclusions on the data collected and analyzed. In addition to analyzing and interpreting the data. Accordingly, Arief (1982, p. 415) says, "This descriptive method also stipulate the nature and circumstances that occur at a particular time". The purpose of this study was to determine the effect of cooperation with the Parent Teacher to increase learning activities of the students.Keywords : Cooperation of teachers with parents, learning activity.